THE EFFECT OF AUDIT OPINION ON MARKET REACTION: GRC AS MODERATOR - I Kadek Jonh Stiawan (ZILLZELL MEDIA PRIMA, 2025)
This study aims to evaluate the effect of audit opinion on market reaction with the implementation of Governance, Risk, and Compliance (GRC) as a moderating variable. The research objects are banking sector companies listed on the Indonesia Stock Exchange during the period 2019–2023. Of the total 47 companies, a purposive sampling technique was used to select 8 companies with observations over 5 years, resulting in 40 observation data. Data were collected through documentation from information available on the IDX website. The analysis was conducted using Moderated Regression Analysis (MRA) with the help of the STATA program. The results show that audit opinion has no effect on market reaction, and the implementation of GRC does not moderate the relationship. This finding indicates that investors in the banking sector tend to focus more on financial information and fundamental company performance, while non-financial factors such as audit opinion and GRC have not been a primary consideration in making investment decisions.